Fenomena Perbedaan Tingkat Kebisingan pada 2 Unit Ruang Tidur: Studi Kasus Rumah Tinggal Peneliti di Tepi Jalan Raya - Suharjanto, Gatot (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Resting is essential to restore the freshness of body both physically and mentally. To optimally gain freshness quality depends on a conducive and comfortable atmosphere during resting time. Architecture also makes convenience factor as a basis for managing comfort zones as classification placement for room specification. One convenience aspect to consider is the noise level, so it is natural that the resting room (bedroom) is placed in zones that are considered quiet, away from the noise level. Theoritically, noise is getting weaker as the sound source distance is getting further. Sound source will also propagate or bounce on a specific object. On contrary, in this case (at the researcher’s residential), the rooms closer to the sound source are even have lower noise levels due to the lower position and barrier block.